2018
DOI: 10.1002/ange.201804614
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Cloke–Wilson Rearrangement

Abstract: Racemic cyclopropyl ketones undergo enantioselective rearrangement to deliver the corresponding dihydrofurans in the presence of a chiral phosphoric acid as the catalyst. The reaction involves activation of the donor‐acceptor cyclopropane substrate by the chiral Brønsted acid catalyst to promote the ring‐opening event, thus generating a carbocationic intermediate that subsequently undergoes cyclization. Computational studies and control experiments support this mechanistic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…11 Although the Lewis acid catalyzed [3 + 2] annulation of aldehydes with 2-arylaziridines has long been known, 12 a catalytic asymmetric version of this reaction has yet to be developed. Inspired by the special substituent effect of the 2-(pmethoxy)phenyl (PMP) group revealed in related elegant works on stereoconvergent transformations of D−A cyclopropanes 3,4 we chose racemic aziridine 1a for the stereoconvergent [3 + 2] annulation study (Table 1). The screen of Lewis acid metal salts with (S)-BINAP as ligand revealed that both the metal center and the anion have profound influence on the reaction (entries 1−6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Although the Lewis acid catalyzed [3 + 2] annulation of aldehydes with 2-arylaziridines has long been known, 12 a catalytic asymmetric version of this reaction has yet to be developed. Inspired by the special substituent effect of the 2-(pmethoxy)phenyl (PMP) group revealed in related elegant works on stereoconvergent transformations of D−A cyclopropanes 3,4 we chose racemic aziridine 1a for the stereoconvergent [3 + 2] annulation study (Table 1). The screen of Lewis acid metal salts with (S)-BINAP as ligand revealed that both the metal center and the anion have profound influence on the reaction (entries 1−6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2,3 Typically, such stereoconvergent processes are believed to proceed via type I DyKAT under Lewis acid catalysis, 3 although type II DyKAT may also be operative as revealed recently in a chiral phosphoric-acid-catalyzed Cloke− Wilson rearrangement reaction. 4 On the other hand, the ring openings of racemic aziridines, which may proceed via either a C−N or a C−C bond cleavage, in a catalytic stereoconvergent way could provide facile access to a variety of chiral nitrogen-containing molecules. 5−7 Current successful enantioconvergent catalytic systems with racemic aziridines have been mainly limited to transition-metal catalysis, including the Pd-catalyzed type I DyKATs of racemic vinyl-aziridines via the formation of chiral π-allyl palladium intermediates 6 (Scheme 1a) and the Ni-catalyzed enantioconvergent reductive cross-coupling of racemic 2-aryl-N-sulfonyl aziridines with aryl iodides (Scheme 1b).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Increasing the strength of the base proved counterproductive because concurrent deprotonation of acidic C−H bonds of cyclopropene occurs, greatly diminishing its electrophilicity. At higher temperature, it was possible to force a thermally induced intramolecular nucleophilic attack in substrate 9, but the resulting donor−acceptor cyclopropane 10 tended toward facile ring-cleavage 10,11 and subsequent decomposition of cyclic imine 11 (Scheme 2). 12…”
Section: Resultsmentioning
confidence: 99%
“…Since the need of high reaction temperature has limited the applicability of the strategy, notable advancements have been achieved at finding milder reaction conditions, including silicon promotion, transition metal catalysis, photocatalysis, and organocatalysis . Recently, Merino and Vicario and coworkers realized the first enantioselective Cloke‐Wilson rearrangements catalyzed by chiral phosphoric acid via dynamic kinetic asymmetric transformation, and chiral dihydrofurans were obtained in high yields and enantioselectivities …”
Section: Methodsmentioning
confidence: 99%